Customer’s satisfaction towards technological advances in personalize banking studies at CIMB Bank Paka, Dungun, Terengganu / Mohamad Nazri Salim @ Bakar, Noraziah Anida Mohd Rashid and Sharifah Suhaila Syed Mohd Nor - Salim @ Bakar, Mohamad Nazri; Mohd Rashid, Noraziah Anida; Syed Mohd Nor, Sharifah Suhaila (2011)
While the entire banking industry is moving fast to improve the IT infrastructure and to implement core-banking solution to integrate the entire banking operations, it is very much important to study in the context of how computerisation has influenced the satisfaction levels of the customers. As IT services have come into the CIMB banking also as well as other banks, not many research works are documented in this technological advance context for personalize banking services in Malaysia, partly in suburban areas.